PENERAPAN PRINSIP – PRNSIP GOOD CORPORATE GOVERNANCE OLEH PT. PLN (PERSERO) PADA MASA PANDEMI COVID-19 DI KOTA PEKANBARU - Malinda, Shella; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
PT. PLN (Persero) as a State-Owned Enterprise (SOEs) have to implement the Good Corporate Governance Principles properly according to regulation of SOEs Minister number Per-01/MBU/2011 about the Implementation of Good Corporate Governance Principles in SOEs. However, in reality the principles are not properly implemented. There were several problems during the COVID-19 pandemic that caused many complaints from the public. The purpose of this research is to evaluate the implementation of the Good Corporate Governance principles by PT. PLN (Persero) during COVID-19 pandemic in Pekanbaru city. This research used a descriptive qualitative research approach. The researcher used the Good Corporate Governance theory from the Organization for Economics Cooperation and Development (OECD) which is based on 5 indicators, namely Transparency, Accountability Responsibility, Independence and Fairness. The data Collection techniques used in this research are interviews, observations and documentation studies. The result of this research indicates that the implementation of the Good Corporate Governance principles by PT. PLN (Persero) during COVID-19 pandemic in Pekanbaru city was not optimal. This can be seen from the poor implementation for three indicators of the Good Corporate Governance based on regulation of SOEs Minister number Per-01/MBU/2011, namely Transparency, Accountability and Responsibility. As for Independence and Fairness, the Principles are well implemented. Keywords : Good Corporate Governance, Public Service, PT. PLN (Persero), State-Owned Enterprise (SOEs), COVID-19 Pandemic.